# Neto-uyo BAN Matsuri since 2018: content moderation and user engagement against hateful contents - Löschke, Ayaka (17th International Conference of the European Association for Japanese Studies (EAJS), 2023)
While people spent more and more time on social media during the recent pandemic, hateful content including comments and videos have posed a growing threat in the world. How did online platforms remove or fail to remove hateful content? Because major social media platforms including YouTube and Twitter have struggled with financial losses in recent years, they began to lay off 30-50% of employees including content moderators in November 2022. It is possible that online platforms will increase the number of content moderators also in Japan. In contrast to Germany, Japan did not adopt a legislation to obligate online platforms to remove hateful content within a specific time frame. Therefore, victims of hateful content must spend much time and money to identify and to sue its authors or uploaders. User engagement against hateful content has received international scholarly attention in recent years, because such user engagement is an increasingly indispensable part of content moderation (Gillespie 2018). Users can collectively and systematically report hateful content that could be regarded as violating the platform guidelines to support commercial moderators in detecting hateful content quickly and accurately. Especially a German case study prompted scholars to theorize about determinants of such user engagement (Porten-Cheé et al. 2020; Ziegele & Naab 2020 etc.). How did Japanese users cope with hateful content? To answer the question, my presentation analyzes the “Neto-uyo BAN Matsuri” (Internet Rightists Ban Festival), an online activism which has reported hateful content on YouTube and Twitter since 2018. It shows the main targets of this activism such as right-wing publicists and entrepreneurs who make full use of traditional and new media and identifies the determinants of the user engagement, based on a qualitative analysis of 3,821 tweets and classification of 1,038 participant
Keywords: media industries; hate speech; user engagement